2018
DOI: 10.1101/481861
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

S-acylated Golga7b stabilises DHHC5 at the plasma membrane to regulate desmosome assembly and cell adhesion

Abstract: S-acylation is the only fully reversible lipid modification of proteins however little is known about how protein Sacyltransferases (PATs) that mediate it are regulated. DHHC5 is a plasma membrane-localised PAT with roles in synaptic plasticity, massive endocytosis and cancer cell growth/invasion. Here we demonstrate that stabilisation of DHHC5 at the plasma membrane requires binding to and palmitoylation of an accessory protein Golga7b. This interaction requires the palmitoylation of the C-terminus of DHHC5 w… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(50 citation statements)
references
References 46 publications
2
48
0
Order By: Relevance
“…Several recent studies have shown that the C-terminal S -acylated cysteines in zDHHC5 ( Fig. 2 ) are important in regulating the distribution of this enzyme between the plasma membrane and internal membranes in nonneuronal cells ( 85 87 ). Indeed, one study reported that S -acylation of these cysteines occurred in response to isoproterenol stimulation, leading to stabilization of zDHHC5 at the plasma membrane ( 85 ).…”
Section: Regulation Of Zdhhc Enzymes By S -Acylatimentioning
confidence: 99%
“…Several recent studies have shown that the C-terminal S -acylated cysteines in zDHHC5 ( Fig. 2 ) are important in regulating the distribution of this enzyme between the plasma membrane and internal membranes in nonneuronal cells ( 85 87 ). Indeed, one study reported that S -acylation of these cysteines occurred in response to isoproterenol stimulation, leading to stabilization of zDHHC5 at the plasma membrane ( 85 ).…”
Section: Regulation Of Zdhhc Enzymes By S -Acylatimentioning
confidence: 99%
“…Golga7b is palmitoylated by zDHHC5 and interacts with the same region of the zDHHC5 C tail as the Na-pump in a palmitoylation-dependent manner. Palmitoylated Golga7b is required for delivery of zDHHC5 to the cell surface as well as recruitment to and palmitoylation of substrates by zDHHC5 23 . When we carried out a detailed proteomic analysis of the proteins in cardiac muscle that interact with NBSP, however, neither Golga7 nor Golga7b were identified 48 .…”
Section: Discussionmentioning
confidence: 99%
“…However, this does not rule out the possibility of zDHHC5 and the Na-pump α-subunit interacting indirectly via an adapter protein. Recently the activity and localization of zDHHC5 in HEK and HeLa cells has been found to be regulated by two closely related proteins, Golga7 47 and Golga7b 23 respectively. Golga7b is palmitoylated by zDHHC5 and interacts with the same region of the zDHHC5 C tail as the Na-pump in a palmitoylation-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…LC-MS/MS analysis was performed and data was processed and quantified as described previously 62 . Briefly, peptides were analysed by nanoflow LC-MS/MS using an Orbitrap Elite (Thermo Fisher) hybrid mass spectrometer equipped with a nanospray source, coupled to an Ultimate RSLCnano LC System (Dionex).…”
Section: Methodsmentioning
confidence: 99%